The state of the cellular link of innate immunity in men depending on type and amount of alcohol consumed - O. S. Kozachuk; L. L. Vorontsova; V. A. Kovalenko (Сучасні медичні технології)
The aim. Study of the state of the cellular link of nonspecific immunity depending on the type and amount of alcohol consumed.